In situ gas foaming based on magnesium particle degradation: A novel approach to fabricate injectable macroporous hydrogels. (February 2020) - Tang, Yanmei; Lin, Sihan; Yin, Shi; Jiang, Fei; Zhou, Mingliang; Yang, Guangzheng; Sun, Ningjia; Zhang, Wenjie; Jiang, Xinquan
Abstract: Injectable hydrogels are attractive biomaterials for cell delivery in tissue engineering. However, the in vivo viability of transplanted cells remains limited. Typically, macroporous structures constructed in hydrogels are utilized to enhance oxygen and nutrients diffusion for cell survival and to promote integration between the material and host tissue. A new gas-foaming method to generate pores was proposed by directly adding Mg particles into cell-laden hydrogel solutions, taking advantage of the H2 gas formed during the degradation of Mg. The optimization design of the size and amount of Mg particles added into the hydrogels was investigated. Improved cell viability and proliferation were demonstrated in the group with Mg particles. Additionally, Mg 2+ ions generated during Mg degradation facilitated the osteogenic differentiation of stem cells encapsulated in hydrogels. Extensive vascularized bone regeneration in the femoral defects of rats revealed that the use of Mg particles as the foaming agent is feasible, endowing injectable hydrogels with optimized porosity and enhanced bioactivity, and providing a new strategy for future designs of porous hydrogels in tissue engineering.